Local Ocular Surface Alterations in Children with Hashimoto's Thyroiditis. (3rd July 2020) - Kiziltoprak, Hasan; Koc, Mustafa; Tekin, Kemal; Hekimoglu, Rumeysa; Inanc, Merve; Yılmaz, Aslıhan Araslı; Elmaoğulları, Selin; Aycan, Zehra
ABSTRACT: Purpose: To evaluate the ocular surface characteristics based on Schirmer's test, tear break-up time (TBUT), and conjunctival impression cytology (CIC) in children with Hashimoto's thyroiditis (HT). Methods: This study included 51 children with HT and 53 control subjects. The ocular surface characteristics of participants were assessed via Schirmer's test, TBUT, and CIC. Conjunctival samples were examined cytologically according to the Nelson grading system. Results: Schirmer's and TBUT results were significantly lower in HT group ( p < .05). All samples in both the study and control groups were evaluated as grade 0 according to the Nelson classification ( p = .841), however, goblet cell density (GCD) was significantly lower in HT group ( p = .001). Schirmer test results were significantly associated with the duration of HT ( p = .025, r = −0.311). Conclusion: Hashimoto's thyroiditis without any ocular complaints may cause ocular surface changes with TBUT and Schirmer's. Although CIC analysis showed similar grading results, GCD was significantly decreased in HT group.